2010 IEEE International Conference on Robotics and Automation 2010
DOI: 10.1109/robot.2010.5509488
|View full text |Cite
|
Sign up to set email alerts
|

Analytical modeling and experimental studies of robotic fish turning

Abstract: Turning is one of the most important maneuvers for biological and robotic fish. In our group's prior work, an analytical framework was proposed for modeling the steady turning of fish, given asymmetric, periodic body/tail movement or deformation. However, the approach was not illustrated with simulation or validated with experiments. The contributions of the current paper are three fold. First, an extension to the modeling framework is made with a more rigorous formulation of the force balance equation. Second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“…One approach is using a single servo to generate asymmetric flapping motion on the tail. Tan et al studied the turning of robotic fish using one precise servo to generate asymmetric flapping [31]. They also found that the robotic fish can achieve better turning performance with a flexible caudal fin, in terms of smaller turning radius, compared to the robotic fish with a rigid caudal fin.…”
Section: Introductionmentioning
confidence: 99%
“…One approach is using a single servo to generate asymmetric flapping motion on the tail. Tan et al studied the turning of robotic fish using one precise servo to generate asymmetric flapping [31]. They also found that the robotic fish can achieve better turning performance with a flexible caudal fin, in terms of smaller turning radius, compared to the robotic fish with a rigid caudal fin.…”
Section: Introductionmentioning
confidence: 99%
“…Meurer et al [32] also employed a similar mechanism in a compliant robotic fish using a nonlinear controller, but with a mechanically coupled actuation system and without considering proprioception. On the other hand, classical approaches for steady turning maneuvers involve changing the center of oscillation of the robot's tail, which require large tail deflections to be effective [33,34]. However, the robot presented in this study has relatively small tail segments with space in between them.…”
Section: Discussionmentioning
confidence: 98%